The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1007/s15010-018-1204-7
|View full text |Cite
|
Sign up to set email alerts
|

Fungal peritonitis in peritoneal dialysis: 5-year review from a North China center

Abstract: FP results in high rates of catheter loss and all-cause mortality in 3 months of follow-up, candida species were the commonest pathogens in our center. Variations of clinical features and susceptibility patterns were observed. Gastrointestinal disorders maybe a potential risk factor for FP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 33 publications
1
42
1
1
Order By: Relevance
“…We then estimated Candida peritonitis by assuming that there were 2 episodes of candidemia per episode of intraabdominal candidiasis in the ICU, based on a large prospective study (20). In addition, we estimated Candida peritonitis in CAPD using data from the First Affiliated Teaching Hospital in Tianjin (21). For RVVC, when prevalence data were not available, we used the rate of women with RVVC from a recent global estimate (22).…”
Section: Analysis Of Data Candidiasis Burden Estimationsmentioning
confidence: 99%
“…We then estimated Candida peritonitis by assuming that there were 2 episodes of candidemia per episode of intraabdominal candidiasis in the ICU, based on a large prospective study (20). In addition, we estimated Candida peritonitis in CAPD using data from the First Affiliated Teaching Hospital in Tianjin (21). For RVVC, when prevalence data were not available, we used the rate of women with RVVC from a recent global estimate (22).…”
Section: Analysis Of Data Candidiasis Burden Estimationsmentioning
confidence: 99%
“…The incidence worldwide is heterogenous with rates varying from 2 to 23.8% [2]. In the United Kingdom an audit study reported a fungal peritonitis rate of 0.0099/patient year from centres not using prophylaxis and a lower rate of 0.0032/patient year in centres using daily oral fluconazole [3]. Despite its rarity fungal peritonitis is important due to its associated higher rates of catheter loss, morbidity and mortality [3].…”
Section: Introductionmentioning
confidence: 99%
“…In the United Kingdom an audit study reported a fungal peritonitis rate of 0.0099/patient year from centres not using prophylaxis and a lower rate of 0.0032/patient year in centres using daily oral fluconazole [3]. Despite its rarity fungal peritonitis is important due to its associated higher rates of catheter loss, morbidity and mortality [3]. Candida species are the commonest pathogen isolated in fungal peritonitis, accounting for 70-90% of the cases described [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations